Fish consumption and its motives in households with versus without self-reported medical history of CVD: A consumer survey from five European countries - Brunsø Karen; Perez-Cueto Federico; Verbeke Wim; Pieniak Zuzanna; De Henauw Stefaan (BMC, 2008)
Abstract Background The purpose of this study was to explore the cross-cultural differences in the frequency of fish intake and in motivations for fish consumption between people from households with (CVD+) or without (CVD-) medical history of cardiovascular disease, using data obtained in five European countries. Methods A cross-sectional consumer survey was carried out in November-December 2004 with representative household samples from Belgium, the Netherlands, Denmark, Poland and Spain. The sample consisted of 4,786 respondents, aged 18-84 and who were responsible for food purchasing and cooking in the household. Results Individuals from households in the CVD+ group consumed fish more frequently in Belgium and in Denmark as compared to those in the CVD- group. The consumption of fatty fish, which is the main sources of omega-3 PUFA associated with prevention of cardiovascular diseases, was on the same level for the two CVD groups in the majority of the countries, except in Belgium where CVD+ subjects reported to eat fatty fish significantly more frequently than CVD- subjects. All respondents perceived fish as a very healthy and nutritious food product. Only Danish consumers reported a higher subjective and objective knowledge related to nutrition issues about fish. In the other countries, objective knowledge about fish was on a low level, similar for CVD+ as for CVD- subjects, despite a higher claimed use of medical information sources about fish among CVD+ subjects. Conclusion Although a number of differences between CVD- and CVD+ subjects with respect to their frequency of fish intake are uncovered, the findings suggest that fish consumption traditions and habits - rather than a medical history of CVD - account for large differences between the countries, particularly in fatty fish consumption. This study exemplifies the need for nutrition education and more effective communication about fish, not only to the people facing chronic diseases, but also to the broader public. European consumers are convinced that eating fish is healthy, but particular emphasis should be made on communicating benefits especially from fatty fish consumption.